Encouraging Active Stress Management among Graduate Students: Formative Research for a Persuasion through the Stages Approach (Global Journal of Medical Research, 2014)
Stress is prevalent among graduate students and can be problematic for their work, academics and health. Interventions aimed at stress management have aided student populations in the past and may be appropriate among graduate students, especially if theoretically driven. An online survey guided by social judgment theory, the transtheoretical model, and perceived behavioral control was conducted to collect formative research for an intervention regarding stress management for graduate students. Although results demonstrate stress is common among this audience and many students are actively managing their stress, negative academic and lifestyle consequences from stress are still abundant. A stage approach through a social norms intervention involving the assistance of faculty may improve this issue.
Keywords: graduate students; stress management; social judgment theory; transtheoretical model; formative intervention research